The Role of Work-Life Balance and Work Environment on Police Job Satisfaction at the East Java Regional Police - Novi Indah Earlyanti; Elvianus Laoli (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2026)
Members of the Indonesian National Police (POLRI) often face long and unpredictable working hours and high job demands, leading to stress, fatigue, and conflicts between work and personal life. Additionally, a less supportive work environment, including facilities, interpersonal relationships among members, and disciplinary pressure, can affect the performance and job satisfaction of POLRI members. These issues form the background of this study, which aims to analyze the influence of work-life balance and the work environment on the job satisfaction of POLRI members in the East Java region. This research uses a quantitative method, collecting data through questionnaires distributed randomly to 367 POLRI members via social media. Data analysis was conducted using validity and reliability tests, classical assumption tests (normality, multicollinearity, heteroscedasticity), and multiple linear regression to examine partial (t-test) and simultaneous (F-test) effects, with the coefficient of determination (R²) measuring the contribution of the independent variables. The results show that both work-life balance and the work environment have a positive and significant influence on the job satisfaction of POLRI members, emphasizing the importance of managing working hours, environmental support, and balancing work and personal life to enhance members' performance and well-being. The study implies that POLRI management needs to improve support for the work environment, manage working hours and workload, and facilitate a balance between work and personal life for members, so that the performance and well-being of POLRI personnel can be optimally enhanced.